Aklimatisasi Benih Ikan Nila (Oreochromis spp) dengan Pencampuran Air Gambut - Tania Serezova Augusta (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
Tilapia fish has now become a commodity most widely cultivated by the people of Central Kalimantan, and especially the City of Palangka Raya. Where is widely cultivated species of fish in cages, ponds, even in tanks that deliberately in the yard. The success of Tilapia fish aquaculture in the peat water depends on the ability of fry in adapting to water turf. These adjustments must begin adjusting to survive until the adjustment to grow and multiply. These adjustment must be made through a particular treatment. In this case tilapia fry must conducted in long time. This acclimatization performed by mixing well water and peat water and expressed in different percentage. This study was conducted to find out the effect of the percentage of mixing peat water and well water as a medium for survival acclimatization tilapia fry. Percentage of peat water ideal in this study were in Group B and Group C with an average mortality reaches 0 %. While Group D was not good because the average mortality by nearly 100 %.